1995
DOI: 10.1136/jcp.48.5.424
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity on chromosome 11 q in breast cancer.

Abstract: Aims-Chromosome llq23 seems to be a site of frequent mutation in cancer. It also contains loci such as ataxia telangiectasia with possible importance in the pathogenesis of breast tumours. The short arm of chromosome 11 has been studied extensively in breast cancer, but the long arm, in particular the distal part, has been studied less frequently. Cytogenetic analysis has shown possible involvement of chromosome llq in breast tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…An increase in Cul5 expression with granulocytic differentiation is not totally unexpected, as overexpression of Cul5 inhibits proliferation in CHO, COS-1, and T47D cell lines (Van Dort et al 2003;Burnatowska-Hledin et al 2004), and Cul5 plays a role in cell fate determination in Drosophila (Ayyub et al 2005). Additional studies also support a putative tumor suppressor role for Cul5 in breast cancer, as the chromosomal location (11q22-23) for Cul5 is associated with loss of heterozygosity (Carter et al 1994;Hampton et al 1994;Gudmundsson et al 1995;Negrini et al 1995;Tomlinson et al 1995;Winqvist et al 1995;Byrd et al 1997;Driouch et al 1998) and there is decreased expression of Cul5 in breast tumor tissues versus matched normal tissues (Fay et al 2003). A 1.6-fold change in Cul5 mRNA expression, and a 6.5-fold change in Cul5 protein expression, may have an important role in cellular processes such as differentiation since a previous study indicated that a less than twofold increase in the expression of another cullin family member, Cul4A, promotes proliferation and attenuates granulocytic differentiation of the PLB-985 human myeloid leukemia cell line .…”
Section: Discussionmentioning
confidence: 91%
“…An increase in Cul5 expression with granulocytic differentiation is not totally unexpected, as overexpression of Cul5 inhibits proliferation in CHO, COS-1, and T47D cell lines (Van Dort et al 2003;Burnatowska-Hledin et al 2004), and Cul5 plays a role in cell fate determination in Drosophila (Ayyub et al 2005). Additional studies also support a putative tumor suppressor role for Cul5 in breast cancer, as the chromosomal location (11q22-23) for Cul5 is associated with loss of heterozygosity (Carter et al 1994;Hampton et al 1994;Gudmundsson et al 1995;Negrini et al 1995;Tomlinson et al 1995;Winqvist et al 1995;Byrd et al 1997;Driouch et al 1998) and there is decreased expression of Cul5 in breast tumor tissues versus matched normal tissues (Fay et al 2003). A 1.6-fold change in Cul5 mRNA expression, and a 6.5-fold change in Cul5 protein expression, may have an important role in cellular processes such as differentiation since a previous study indicated that a less than twofold increase in the expression of another cullin family member, Cul4A, promotes proliferation and attenuates granulocytic differentiation of the PLB-985 human myeloid leukemia cell line .…”
Section: Discussionmentioning
confidence: 91%
“…While deletions of 11q22-25 have been reported in a broad variety of cancers, including those originating in the breast, ovary, lung, bladder, and prostate (Keldysh et al, 1993;Foulkes et al, 1993;Hampton et al, 1994;Iizuka et al, 1995;Negrini et al, 1995;Tomlinson et al, 1995;Winqvist et al, 1995;Gudmundsson et al, 1995;Shaw et al, 1995;Gabra et al, 1996;Evans et al, 1996;Dahiya et al, 1997), as well as from nevi (Tomlinson et al, 1993(Tomlinson et al, , 1996Walker et al, 1995;Herbst et al, 1995), molecular studies have generally failed to identify a consistent critical region and have led to the conclusion that multiple tumor suppressor genes probably exist within this region. DeĀ®ning the location of these putative genes by solely positional means has been problematic, even to the extent that independent LOH studies performed on the same tumor type (e.g., breast cancer) have not yielded consistent results or been successful in pinpointing the exact location of a tumor suppressor gene (Hampton et al, 1994 ;Iizuka et al, 1995;Negrini et al, 1995;Tomlinson et al, 1995;Winqvist et al, 1995;Gudmundsson et al, 1995). Molecular Ā®ndings on melanoma are no exception, where 26 Ā± 58% of metastatic melanomas have been determined to harbor predominantly large (544 cM) deletions on 11q22-25 (Tomlinson et al, 1993(Tomlinson et al, , 1996Walker et al, 1995;Herbst et al, 1995, unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…Deletions or rearrangements of chromosome 11, which occur in 26 Ā± 58% of metastatic melanomas (Tomlinson et al, 1993(Tomlinson et al, , 1996Walker et al, 1995;Herbst et al, 1995), are also frequently observed in other cancers, including those originating in the breast, ovary, lung, bladder, colon, and prostate (Keldysh et al, 1993;Foulkes et al, 1993;Hampton et al, 1994;Iizuka et al, 1995;Negrini et al, 1995;Tomlinson et al, 1995;Winqvist et al, 1995;Gudmundsson et al, 1995;Shaw et al, 1995;Gabra et al, 1996;Evans et al, 1996;Dahiya et al, 1997). To date, loss of heterozygosity (LOH) studies on melanoma tumors have been relatively unsuccessful in identifying a conĀ®ned region of loss on chromosome 11 (Herbst et al, 1995) and the most recent report suggests that multiple melanoma tumor suppressor genes may exist on this chromosome (Tomlinson et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple regions within human chromosome 11q23 are frequently deleted or translocated in several types of human cancer, including leukemia (10), breast cancer (11), lung cancer (12), cervical uterus cancer (13), squamous cell carcinoma of head and neck (14), melanoma (15), and colorectal cancer (16). Recently, I have cloned and characterized the MFRP gene on 11q23 region, encoding a membrane-type Frizzled-related protein (17).…”
mentioning
confidence: 99%